Level of Physical Freshness Extracurricular Volleyball SMAN 1 Bangko: Tingkat Kesegaran Jasmani Ekstrakurikuler Bola Voli SMAN 1 Bangko - Suci Muhammad Ridho; Mimi Yulianti (Badnur Medisa Group, 2022)
The purpose of this study was to determine the level of physical fitness in volleyball extracurricular at SMAN 1 Bangko. This type of research is descriptive quantitative with a population of students extracurricular volleyball SMAN 1 Bangko totaling 12 people. The sampling technique used was total sampling, so that this study amounted to 12 people. The instrument used in this study was the Indonesian Physical Fitness Level (TKJI) 16-19 years old test, namely running 60 meters, lifting elbows bent, lying down for 60 seconds, jumping straight, running 1200 meters. The data analysis technique used is the conversion of physical fitness test scores. Based on the results of data processing, it can be concluded that the level of physical fitness of volleyball extracurricular at SMAN 1 Bangko is classified as Less Once with an average of 8.